Pengembangan Elektronik-Sistem Akuntabilitas Kinerja Instansi Pemerintah untuk Dinas Perindustrian Kota Malang - Handoyo Saputra; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Malang Industrial Department has duty to arrange strategic plan for measure it's work achievement. To measure goverment department's achievement, goverment has develop a system called â€œSistem Akuntabilitas Kinerja Instansi Pemerintahâ€ (SAKIP). The problem that occured in SAKIP realization is when collecting data of work achievement is to long. The other problem is the chief department can not knowing all work achievement in realtime. For now, there is no information system for manage SAKIP realization yet. Management information system make it possible for organizations to get the right information to the right person at the right time by enhancing the interaction between the organization's workers. Because of that, in this thesis project will be depeloping a web based information system for manage SAKIP realization that has a prime function to record, measure and report work achievement's result. For developing this software, will be using waterfall methodology. In waterfall model, there are 5 phases. First phase is analysis, then planning, implementation, testing and the last is maintenance. Functionality testing for this software is using white-box and black-box testing approach. The result of functionality testing indicate that this software function is appropriate with it's specification. Compatibility testing indicate that this software can running well on all different browser